HARBIY XIZMATCHILAR VA HARBIY JAMOANI O’RGANISHNING PSIXOLOGIK NAZARIY ASOSLARI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the psychological theoretical foundations of studying military personnel and military teams from a systematic perspective. The research explores modern approaches in military psychology, focusing on the psychological interactions between individuals and groups, leadership, motivation, stress resilience, and adaptation processes. Special attention is given to the interaction of individual and socio-psychological factors within the military environment. The study proposes theoretical models and conceptual frameworks aimed at improving the effectiveness of military teams through psychological research methods. The findings contribute to strengthening the psychological preparedness of military personnel and optimizing collective performance.